Design and fabrication of a mechanical grass cutter / Syed Abdullah Syed Hasan - Syed Hasan, Syed Abdullah (2024)
The development of a lawn cutter that runs without fuel or power is a development in the realm of gardening and landscaping. Gardeners can use this grass cutter to trim the grass on their lawns or even in remote areas without access to electricity. The use of fuel-powered grass cutter has negative environmental and economic impacts. In addition, the noise pollution caused by these machines can be a nuisance to communities. There is a need for a grass cutter that runs without fuel or electricity sources to mitigate these issues. The goal of this project is to design and build a grass cutter that does not need fuel or electricity. The project's goal is to create a prototype lawn cutter using SolidWorks. Through the utilisation of created torque, the cutting head mechanism functions flawlessly. To cut grass efficiently, the setup rotates the shaft using a variety of wheel arrangements. This method guarantees a more orderly and silent grass-cutting procedure. Wide-ranging advantages are anticipated from this discovery, such as a decrease in noise and air pollution and the maintenance expenses associated with conventional lawn mowers. The goal is to create a working prototype of an energy-efficient grass cutter that can effectively replace the current generation of lawn mowers that run on petrol.